Contemporary shamanism and alternative spirituality : exploring relationships and intersections - Dyndová, Helena (Religio, 2024)
Contemporary shamanism, often referred to as neo-shamanism, is a popular spiritual practice within the modern landscape of non-institutionalized religiosity. This paper explores the relationship between contemporary shamanism and alternative spirituality (formerly also labelled as the New Age) in depth, underlining that contemporary shamanism owes much of its success to its compatibility with the religious worldviews of today’s era. In this sense, contemporary shamanism works similarly to "native" shamanisms, acting not as an independent religious system but as a configuration within distinct sociocultural and religious contexts. The article discusses the discursive transformation over the past three centuries that has led to the contemporary perception of the shaman as a healer, stressing the pivotal role of Michael Harner and his Foundation for Shamanic Studies in shaping and establishing contemporary shamanism. Drawing from extensive fieldwork in neo-shamanic communities, it shows how contemporary shamanism has adapted and "translated" the three key motifs of alternative spirituality (the concepts of energy, holism, and the soul) and uses them in healing practice. Ultimately, this article posits how contemporary shamanism fits within the broader tapestry of alternative spirituality, emphasizing that its adaptability is an asset, not an inauthentic glitch.